Nitrogen addition alters plant growth in China’s Yellow River Delta coastal wetland through direct and indirect effects - Zhang, Liwen; Zhao, Lianjun; Yi, Huapeng; Lan, Siqun; Chen, Lin; Han, Guangxuan (Frontiers in Plant Science, 2022)
In the coastal wetland, nitrogen is a limiting element for plant growth and reproduction. However, nitrogen inputs increase annually due to the rise in nitrogen emissions from human activity in coastal wetlands. Nitrogen additions may alter the coastal wetlands’ soil properties, bacterial compositions, and plant growth. The majority of nitrogen addition studies, however, are conducted in grasslands and forests, and the relationship between soil properties, bacterial compositions, and plant growth driven by nitrogen addition is poorly understood in coastal marshes. We conducted an experiment involving nitrogen addition in the Phragmites australis population of the tidal marsh of the Yellow River Delta. Since 2017, four nitrogen addition levels (N0:0 g • m-2 • year-1, N1:5 g • m-2 • year-1, N2:20 g • m-2 • year-1, N3:50 g • m-2 • year-1) have been established in the experiment. From 2017 to 2020, we examined soil properties and plant traits. In 2018, we also measured soil bacterial composition. We analyzed the effect of nitrogen addition on soil properties, plant growth, reproduction, and plant nutrients using linear mixed-effect models. Moreover, structural equation modeling (SEM) was utilized to determine the direct and indirect effects of nitrogen addition, soil properties, and bacterial diversity on plant growth. The results demonstrated that nitrogen addition significantly affected plant traits of P. australis. N1 and N2 levels generally resulted in higher plant height, diameter, leaf length, leaf breadth, and leaf TC than N0 and N3 levels. Nitrogen addition had significantly impacted soil properties, including pH, salinity, soil TC, and soil TS. The SEM revealed that nitrogen addition had a direct and positive influence on plant height. By modifying soil bacterial diversity, nitrogen addition also had an small indirect and positive impact on plant height. However, nitrogen addition had a great negative indirect impact on plant height through altering soil properties. Thus, nitrogen inputs may directly enhance the growth of P. australis at N1 and N2 levels. Nonetheless, the maximum nitrogen addition (N3) may impede P. australis growth by reducing soil pH. Therefore, to conserve the coastal tidal marsh, it is recommended that an excess of nitrogen input be regulated.